PoreDesigner for tuning solute selectivity in a robust and highly permeable outer membrane pore - Ratul Chowdhury (Nature Portfolio, 2018)
Monodisperse angstrom-sized membrane proteins, found in biological membranes, are difficult to implement in synthetic industrial membranes. Here authors present a pore design procedure, to redesign the robust beta-barrel Outer Membrane Protein F (OmpF) with specific solute selectivity.